2018
DOI: 10.1086/698211
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Influences on Partial Self-Incompatibility in Lythrum salicaria (Lythraceae)

Abstract: Premise of research. Angiosperms are commonly classified as self-incompatible or self-compatible. This dichotomy has influenced research on the ecological and demographic consequences of colonization because of the predicted benefits of self-compatibility for establishment at low density. Some individuals of self-incompatible species, however, exhibit partial self-incompatibility (PSI), meaning that they set variable amounts of seed following self-pollination. Here, we investigate genetic and environmental com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 88 publications
0
6
0
1
Order By: Relevance
“…Among our study populations, population sizes ranged from 8-187 individuals with a wide range of morph frequencies (Table 1). Second, controlled pollination studies have consistently revealed that L. salicaria exhibits partial trimorphic incompatibility, with plants of the M-morph more often self-compatible and those of the S-morph most strongly self-incompatible (Darwin 1864;Stout 1923;O'Neil 1994;Mal et al 1999;Colautti et al 2010;Balogh and Barrett 2018). This variation in demography and incompatibility expression raised the question of whether these features might influence patterns of mating and fertility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among our study populations, population sizes ranged from 8-187 individuals with a wide range of morph frequencies (Table 1). Second, controlled pollination studies have consistently revealed that L. salicaria exhibits partial trimorphic incompatibility, with plants of the M-morph more often self-compatible and those of the S-morph most strongly self-incompatible (Darwin 1864;Stout 1923;O'Neil 1994;Mal et al 1999;Colautti et al 2010;Balogh and Barrett 2018). This variation in demography and incompatibility expression raised the question of whether these features might influence patterns of mating and fertility.…”
Section: Discussionmentioning
confidence: 99%
“…Populations of L. salicaria are commonly tristylous and the species possesses a trimorphic incompatibility system that generally prohibits self-and intramorph fertilization. However, populations commonly exhibit partial self-incompatibility, with the M-morph displaying the weakest incompatibility and the S-morph the strongest, based on controlled self-and cross-pollinations (Darwin 1877;Colautti et al 2010;Balogh and Barrett 2018). At present, it is unclear whether variation in partial self-incompatibility influences mating patterns in populations of L. salicaria.…”
Section: Study Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Partial self‐incompatibility in the M‐morph also occurs in most populations of Lythrum salicaria (Colautti et al ., ) with considerable variation among plants in the degree of self‐compatibility. Individual variation is repeatable across years and has a weak heritable basis, and M‐morph offspring within segregating selfed families of M‐morph parents are significantly more self‐compatible than plants of the L‐morph (Balogh & Barrett, ). This difference in morph‐specific expression may result from the pleiotropic effects of genes controlling tristylous characters, with variation among individuals caused by genetic modifiers either linked or unlinked to the M ‐locus.…”
Section: Variations On a Themementioning
confidence: 99%
“…L. salicaria tohumları yaklaşık 1 mm boyunda olup olgun bireylerde yılda 2 milyonun üzerinde tohum elde edilmektedir [11]. Kendine tozlaşan tohumlar özellikle yağmur, rüzgar, sulak alanda yaşayan hayvanlar ve su kuşlarının dışkıları ile taşınırlar [12]. Tohumlar suyun yüzeyinde bulunur ve oluşan su akımlarıyla kolaylıkla taşınabilmektedir.…”
Section: Introductionunclassified